Targeting T cell exhaustion: emerging strategies in non-small cell lung cancer - Liu, Xianqiang; Xi, Xiaowei; Xu, Shengshan; Chu, Hongyu; Hu, Penghui; Li, Dong; Zhang, Bin; Liu, Hejie; Jiang, Tianxiao; Lu, Zhuming (Frontiers in Immunology, 2024)
Lung cancer continues to be a major contributor to cancer-related deaths globally. Recent advances in immunotherapy have introduced promising treatments targeting T cell functionality. Central to the efficacy of these therapies is the role of T cells, which are often rendered dysfunctional due to continuous antigenic stimulation in the tumor microenvironment–a condition referred to as T cell exhaustion. This review addresses the critical challenge of T cell exhaustion in non-small cell lung cancer (NSCLC), offering a detailed examination of its molecular underpinnings and the resultant therapeutic ineffectiveness. We synthesize current knowledge on the drivers of T cell exhaustion, evaluate emerging strategies for its reversal, and explore the potential impact of these insights for enhancing the clinical efficacy of immunotherapies. By consolidating reported clinical trials and preclinical studies, this article highlights innovative approaches to modulate immune responses and improve patient outcomes, thus providing a roadmap for future research and therapeutic development in lung cancer immunotherapy.